A Pilot Study On The Integration Of Islamic Building Principles In The Design Of Student-Centered Campus Building - Azhani Abd Manaf; Nur Aina Farhanah Mohd Suffian; Elina Mohd Husini; Madihah Mat Idris; Wan 'Iffah Wan Ahmad Nizar (Universiti Sains Islam Malaysia, 2024)
Date: 9 September 2021 Platform: MSTeams, USIM Nilai, Negeri Sembilan, Malaysia.